Grading of Potato Chips According to Their Sensory Quality Determined by Color - Skurtys-Olivier , F (2012)
Potato chips were classified in quality categories according to their color after frying at oil temperatures (120, 140, 160, and 180 ± 1 °C) and undergoing some pre-treatments (control or unblanching, blanching, and blanching plus drying). For each oil temperature, six time intervals were considered since the beginning of the frying process until the corresponding time at which potato slices reached a moisture content of 2%. In order to define quality categories according to the surface color, we worked with 79 frequent consumers of potato chips who classified the color scores of the potato chip photographs located in a standard color chart in the following categories: (1) desirable color, (2) still acceptable color and (3) nondesirable color. A sensory panel was formed with 12 judges who were selected according to simple tests of color ordering. This sensory panel evaluated the samples processed at different oil temperatures, frying times, and pre-treatments based on the standard color chart previously mentioned. For each measured point, the score from the color standard chart indicated for more than 50% of the panel members was selected. Finally, time-temperature modeling was achieved in order to get potato chip with the best color surface for the three pre-treatments tested. © 2011 Springer Science + Business Media, LLC.